Angular 5 (formerly Angular 2) : the complete guide (Packt Publishing, 2018)
"This course starts from scratch, you neither need to know Angular 1 nor Angular 2! Angular 5 is simply the latest version of Angular 2. Join the most comprehensive and popular Angular course, because now is the time to get started! From Setup to Deployment, this course covers it all! You'll learn all about Components, Directives, Services, Forms, Http Access, Authentication, Optimizing an Angular App with Modules and Offline Compilation and much more - and in the end: you'll learn how to deploy an application! But that's not all! This course will also show you how to use the Angular CLI and features a complete project, which allows you to practice the things learned throughout the course! Angular is one of the most modern, performance-efficient and powerful frontend frameworks you can learn as of today. It allows you to build great web apps which offer awesome user experiences! Learn all the fundamentals you need to know to get started developing Angular applications right away. TypeScript is the main language used by the official Angular team and the language you'll mostly see in Angular tutorials. It's a superset to JavaScript and makes writing Angular apps really easy. Using it ensures, that you will have the best possible preparation for creating Angular apps. Check out the free videos for more information."--Resource description page